High performance perovskite sub-module with sputtered SnO2 electron transport layer - Bai, Guangfeng; Wu, Zhengli; Li, Jing; Bu, Tongle; Li, Wangnan; Li, Wei; Huang, Fuzhi; Zhang, Qi; Cheng, Yi-Bing; Zhong, Jie (Elsevier, 2019)
Hybrid perovskite solar cells (PSC) have gained stupendous achievement in single/tandem solar cell, semitransparent solar cell and flexible devices. Aiming for potential commercialization of perovskite photovoltaic technology, up scalable processing is crucial for all function layers in PSC. Herein we present a study on room temperature magnetron sputtering of tin oxide electron transporting layer (ETL) and apply it in a large area PSC for low cost and continues manufacturing. The SnO2 sputtering targets with varied oxygen and deposition models are used. Specifically, the working gas ratio of Ar/O2 during the radio frequency sputtering process plays a crucial role to obtain optimized SnO2 film. The sputtered SnO2 films demonstrate similar morphological and crystalline properties, but significant varied defect states and carrier transportation roles in the PSC devices. With further modification of thickness of SnO2, the PSCs based on sputtered SnO2 ETL shows a champion efficiency of 18.20% in small area and an efficiency of 14.71% in sub-module with an aperture area of 16.07 cm2, which is the highest efficiency of perovskite sub module with sputtered ETLs.
Keywords: Magnetron; Tin oxide; Perovskite solar cell; Module; High efficiency